Investigation of mechanical properties, remineralization, antibacterial effect, and cellular toxicity of composite orthodontic adhesive combined with silver-containing nanostructured bioactive glass - Massoud Seifi; Fatemeh Eskandarloo; Parisa Amdjadi; Abbas Farmany (BMC, 2024)
Abstract Background The formation of white spots, which represent early carious lesions, is a major issue with fixed orthodontics. The addition of remineralizing agents to orthodontic adhesives may prevent the formation of white spots. The aim of this study was to produce a composite orthodontic adhesive combined with nano-bioactive glass-silver (nBG@Ag) for bracket bonding to enamel and to investigate its cytotoxicity, antimicrobial activity, remineralization capability, and bond strength. Methods nBG@Ag was synthesized using the sol-gel method, and characterized using transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy with an attenuated total reflectance attachment (ATR-FTIR). The cytotoxicity test (MTT) and antimicrobial activity of adhesives containing 1%, 3%, and 5% (wt/wt) nBG@Ag were evaluated, and the shear bond strength of the adhesives was measured using a universal testing machine. Remineralization was assessed through microhardness testing with a Vickers microhardness tester and scanning electron microscopy (SEM). Statistical analyses were conducted using the Shapiro-Wilk test, Levene test, one-way ANOVA, Robust-Welch test, Tukey HSD method, and two-way ANOVA. Results The biocompatibility of the adhesives was found to be high, as confirmed by the lack of significant differences in the cytotoxicity between the sample and control groups. Discs made from composites containing nBG@Ag exhibited a significant reduction in the growth of Streptococcus mutans (p < 0.05), and the antibacterial activity increased with higher percentages of nBG@Ag. The shear bond strength of the adhesives decreased significantly (p < 0.001) after the addition of nanoparticles, but it remained above the recommended value. The addition of nBG@Ag showed improvement in the microhardness of the teeth, although the differences in microhardness between the study groups were not statistically significant. The formation of hydroxyapatite deposits on the tooth surface was confirmed through SEM and energy-dispersive X-ray spectroscopy (EDX). Conclusion Adding nBG@Ag to orthodontic adhesives can be an effective approach to enhance antimicrobial activity and reduce enamel demineralization around the orthodontic brackets, without compromising biocompatibility and bond strength.